Imaging and Interpretation of Axial Spondylarthritis: The Radiologist's Perspective—Consensus of the Arthritis Subcommittee of the ESSR - Schueller-Weidekamm, Claudia; Mascarenhas, Vasco V.; Sudol-Szopinska, Iwona; Boutry, Nathalie; Plagou, Athena; Klauser, Andrea; Wick, Marius; Platzgummer, Hannes; Jans, Lennart; Mester, Adam; Kainberger, Franz; Aström, Gunnar; Guglielmi, Giuseppe; Eshed, Iris (Seminars in Musculoskeletal Radiology, 2014)
This article reflects the radiologist's perspective on the imaging and interpretation of axial spondylarthritis (SpA). The arthritis subcommittee of the European Society of Skeletal Radiology provides a consensus for the following questions: When and how should we image? How should we analyze the images? How should we interpret the imaging findings? To answer these questions, we address the indications in imaging axial SpA and the different imaging techniques, with a special focus on magnetic resonance imaging protocols. The value of different imaging modalities is discussed. For adequate image analysis, knowledge of the anatomy and the pathologic changes in chronic and acute inflammation of the sacroiliac joints and the spine is mandatory. Differential diagnoses of inflammatory lesions of the sacroiliac joints and the spine are addressed due to their importance in image interpretation.
Keywords: spondylarthritis; magnetic resonance imaging; sacroiliitis; diagnosis